An efficient and wide angle coupling of light to a thin film holographic optical element - Mei-Li Hsieh; Zih Fan Chen; Shiuan-Huei Lin; Shawn-Yu Lin (Scientific Reports)
Abstract In this paper, a new method is proposed to achieve wide-angle and efficient coupling of light into a thin film, holographic optical element (HOE). The coupling is based on diffraction of light (the probe beam) by a holographic element. Analytically, we find, when the probe beam follows a specific angular orbit, Bragg conditions for diffraction can be satisfied and the maximum diffraction efficiency expected. As an experimental test of the proposed idea, such a HOE device has been successfully realized. Our result indicates that a highly efficient diffraction (> 80%) can be achieved for a broad range of light incident angle when the angle is along the designed angular orbit. This finding would open up a new possibility for concentrated solar panel application that is both efficient, low cost, and for a broad incident angle of sunlight.